The Endovenous Laser Therapy for the Management of Varicose Veins - Kaushal, Prashant; San, Shen Xuan (Birat Journal of Health Sciences, 2018)
Introduction: Varicose veins of the lower limb are common condition affecting majority of people worldwide and has great effect on quality of life. The definitive therapy being surgery with stripping of the veins which is associated with surgical complications, prolong recovery time and significant recurrence. Endovenous laser therapy (EVLT) is a minimally invasive procedure which is widely used for the treatment of varicose veins with excellent results. Objective: To evaluate the safety and efficacy of EVLT for the management of varicose veins. Methodology: This was a prospective study of 40 patients who underwent endovenous laser therapy at the affiliated hospital of Inner Mongolia University for the Nationalities from October 2016 to September 2017. All patients with primary symptomatic varicose veins with sapheno-femoral incompetence or great saphenous vein (GSV) reflux were included in the study. The patient's information and data were recorded during the hospital stay in the proforma for EVLT with the informed consent. The variables used were mean operating time, intra-operative blood loss, duration of hospital stay, return to normal activity, complications and the recanalization. Following discharge, the patients were followed up to six months. Results: Forty patients with unilateral varicose veins were treated with EVLT. There were 24 female and 16 male with mean age of 52 yrs and the majority of patients having symptoms for more than five years. The mean operative time and intra-operative blood loss were 80 minutes and 52 ml respectively. The mean duration of hospital stay was 2.5 days with 90% patients returning to the normal activity in 10 days. Swelling and indurations were the most common complication in 10 patients followed by hypoesthesia in 8, ecchymosis in 7 and skin burn in 4 patients. Conclusion: EVLT seems to be safe and effective minimally invasive procedure with excellent clinical outcome in terms of lower postoperative pain, early return to normal activities and fewer complications. However large sample size with long follow up study should be conducted for evaluating long term benefits. BJHS 2018;3(2)6:437-442.